Association of Biofilm Formation with Fluconazole Susceptibility in Candida Urinary Isolates - Ronald A Parubak; Noorhamdani AS; Dewi Retnoningsih (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. This study aims to investigate the association between biofilm formation by Candida spp. and in vitro fluconazole susceptibility in urinary isolates from intensive care unit (ICU) patients with indwelling urinary catheters, while characterising species distribution, biofilm formation, and susceptibility patterns. Methods. This cross-sectional study included 44 Candida spp. isolates recovered from urine samples of ICU patients catheterised for more than 48 hours. Species identification and fluconazole susceptibility testing were performed using the VITEK 2 system, and biofilm formation was assessed using a microtiter plate assay. Demographic characteristics, comorbidities, and catheterisation duration were obtained from medical records. Results. Candida albicans was the most frequent species (40.9%), followed by Candida tropicalis (25.0%), Candida glabrata (20.5%), and Candida parapsilosis (13.6%). Half of the isolates (22/44) formed biofilms, predominantly weak, with only a small proportion demonstrating moderate biofilm formation. Fluconazole susceptibility was observed in 16 of 22 (72.7%) biofilm-forming isolates and 17 of 22 (77.3%) non-biofilm-forming isolates, while resistance was identified in 6 of 22 (27.3%) and 5 of 22 (22.7%), respectively. No significant association was found between biofilm formation and fluconazole susceptibility (χ² = 0.121; p = 0.728). Conclusion. In this single-centre ICU cohort, biofilm formation among urinary Candida isolates was common but predominantly weak and was not significantly associated with in vitro fluconazole susceptibility. These findings should be interpreted cautiously, given the cross-sectional design and in vitro nature of the study. Larger multicentre studies are warranted to clarify the clinical relevance of Candida biofilm formation in candiduria.